Neglected extra-articular manifestations in rheumatoid arthritis patients with normal body mass index: reduced skeletal muscle overlapping overfat - Jian-Zi Lin; Chu-Tao Chen; Jian-Da Ma; Ying-Qian Mo; Qian-Hua Li; Le-Feng Chen; Ze-Hong Yang; Wan-Mei Cheng; Xiao-Ling He; Dong-Hui Zheng; Lie Dai (SAGE Publishing, 2020)
Background: Chronic inflammation in rheumatoid arthritis (RA) can induce reduced muscle mass (myopenia) and ectopic fat deposition probably showing normal body mass index (BMI). We aimed to investigate their body composition (BC) characteristics and clinical significance. Methods: BMI and BC were collected in consecutive RA patients and control subjects. Myopenia was defined by appendicular skeletal muscle mass index (ASMI) ⩽7.0 kg/m 2 in men and ⩽5.7 kg/m 2 in women. Overfat was defined by body fat percentage (BF%) as ⩾25% for men and ⩾35% for women. Results: There were 620 RA patients (57.6% with normal BMI) and 2537 control subjects (62.5% with normal BMI) recruited. After 1:1 age and sex matching with control subjects, RA patients with normal BMI ( n  = 240) showed significantly higher prevalence of myopenia (43.3% versus 22.1%) and overfat (19.2% versus 7.1%) as well as myopenia overlapping overfat (17.1% versus 3.3%). In all RA patients with normal BMI ( n  = 357), there were 18.2% patients with myopenia overlapping overfat who had the worst radiographic scores and highest rates of previous glucocorticoid treatment and hypertension. Compared with those without, normal BMI RA patients with previous glucocorticoid treatment (24.4% versus 10.3%) or hypertension (27.8% versus 13.6%) had a higher rate of myopenia overlapping overfat. Previous glucocorticoid treatment [odds ratio (OR) = 2.844, 95% confidence interval (CI) 1.441-5.614] and hypertension (OR = 2.452, 95% CI 1.283-4.685) were potential associated factors of myopenia overlapping overfat in RA patients with normal BMI. Conclusion: Myopenia overlapping overfat is an important extra-articular manifestation which should not be ignored in RA patients with normal BMI, especially with glucocorticoid treatment and hypertension.